A Generalized Version of Polynomial Convex Functions and Some Interesting Inequalities with Applications. (1st April 2023) - Liu, Xiaogang; Aslam, Kiran Naseem; Saleem, Muhammad Shoaib; Ren, Shuili
Abstract : In this article, we introduce a general class of convex functions and proved some of its basic properties. We establish Hermite-Hadamard type inequalities as well as fractional version of Hermite-Hadamard type inequalities by using Riemann-Liouville integral operator. At the end, some application to special means of real numbers are also given. It can be observed from the remarks given in this paper that several exiting results of ligature can be obtained immediacy from our results by taking suitable involved parameters.